Integrating Artificial Intelligence into Personalized Ideological and Political Education: Practices and Reflections (London Journal of Research In Humanities and Social Sciences, 2025)
With the advent of the digital era, Artificial Intelligence (AI) technology has demonstrated significant potential and posed challenges in the field of education. This study aims to delve into the application and impact of AI technology in personalized ideological and political education within higher education curricula. Firstly, it analyzes the current state of AI applications in curriculum-based ideological and political education and the main challenges faced. Further, through empirical research, the paper explores how AI technology empowers and aids professional courses, making the teaching of professional knowledge and ideological content more intuitive, vivid, and efficient, while constructing new models of "Intelligent+" professional courses and "+Intelligent" ideological and political education. The study also evaluates the effectiveness of these technologies in personalized teaching and their specific impact on students' ideological and political qualities. Finally, based on reflections and summaries of practical outcomes, it proposes optimization strategies for personalized ideological and political education assisted by AI. This research provides new perspectives and practical guidelines for personalized ideological and political education in higher education in the digital age, aiming to promote educational innovation and development to better meet future educational needs.
Keywords: Reality.; perceptual presence; experience of reality; subjective veridicality; process; pure consciousness states; Artificial Intelligence; Curriculum Ideological and Political Educationl; Personalized Teaching; Innovative Teaching Models